2019
DOI: 10.3897/zookeys.832.32257
|View full text |Cite
|
Sign up to set email alerts
|

DNA barcoding of British mosquitoes (Diptera, Culicidae) to support species identification, discovery of cryptic genetic diversity and monitoring invasive species

Abstract: Correct mosquito species identification is essential for mosquito and disease control programs. However, this is complicated by the difficulties in morphologically identifying some mosquito species. In this study, variation of a partial sequence of the cytochromecoxidase unit I (COI) gene was used for the molecular identification of British mosquito species and to facilitate the discovery of cryptic diversity, and monitoring invasive species. Three DNA extraction methods were compared to obtain DNA barcodes fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
48
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(53 citation statements)
references
References 57 publications
5
48
0
Order By: Relevance
“…Thus, information about their diversity and host-feeding patterns is crucial to understand parasite-host interactions and the ecology of associated pathogens [30]. DNA barcoding is an important tool in biodiversity studies [53][54][55][56][57]. Thereby, barcoding also helped to identify cryptic and new Culicoides species [58][59][60].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, information about their diversity and host-feeding patterns is crucial to understand parasite-host interactions and the ecology of associated pathogens [30]. DNA barcoding is an important tool in biodiversity studies [53][54][55][56][57]. Thereby, barcoding also helped to identify cryptic and new Culicoides species [58][59][60].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, successful sequencing of 1040 engorged insects demonstrated that barcoding is a useful tool for both, Culicoides and host identification. However, it must be considered that the different genetic markers can have pitfalls and do not necessarily reflect morphological differences [56,61], i.e. using a single marker might be insufficient for an accurate identification of species.…”
Section: Discussionmentioning
confidence: 99%
“…Congeneric groupings were also well‐separated in the NJ tree supporting our morphological identifications. Although cases of misidentification in DNA barcoding studies are not uncommon, this could have serious implications for end users of reference libraries (Collins & Cruickshank, ; Hernández‐Triana et al, ). It appears that the incongruence observed in the NJ analysis for Pa. abonnenci (Figure ) seems to be one of such a case.…”
Section: Discussionmentioning
confidence: 99%
“…In order to molecularly support our morphological identification, we employed the COI DNA barcoding approach as detailed in Hebert et al [10]. DNA extraction was performed using a modified Hotshot technique as in Hernández-Triana et al [11]. In short, two whole larvae were placed directly into 50 μL of alkaline lysis buffer in a 96-well plate and then sonicated in a water bath for 15 min.…”
Section: Case Reportmentioning
confidence: 99%
“…e lysate was stored at − 80°C until analysis, while the larvae were preserved in ethanol 99%. For amplification of the COI DNA barcoding region, we used the PCR forward forward primer LCO1490 (5′-GGT CAA CAA ATC ATA AAG ATA TTG G-3′) and reverse primer HCO 2198 (5′-TAA ACT TCA GGG TGA CCA AAA AAT CA-3′) which amplify the 658-bp target region of the COI gene [10,11]. PCR products were obtained using the following reaction mix in a final volume 50 μL: albumin (20 mg/mL).…”
Section: Case Reportmentioning
confidence: 99%